Effect of Patient Navigation on Breast Cancer Screening Among African American Medicare Beneficiaries: A Randomized Controlled Trial - Marshall, Jessie Kimbrough (J Gen Intern Med, 2015)
BACKGROUND: There is growing evidence that patient navigation improves breast cancer screening rates; however, there are limited efficacy studies of its effect among African American older adult women. OBJECTIVE: To evaluate the effect of patient navigation on screening mammography among African American female Medicare beneficiaries in Baltimore, MD. DESIGN: The Cancer Prevention and Treatment Demonstration (CPTD), a multi-site study, was a randomized controlled trial conducted from April 2006 through December 2010. SETTING: Community-based and clinical setting. PARTICIPANTS: The CPTD Screening Trial enrolled 1905 community-dwelling African American female Medicare beneficiaries who were ≥65 years of age and resided in Baltimore, MD. Participants were recruited from health clinics, community centers, health fairs, mailings using Medicare rosters, and phone calls. INTERVENTIONS: Participants were randomized to either: printed educational materials on cancer screening (control group) or printed educational materials + patient navigation services designed to help participants overcome barriers to cancer screening (intervention group). MAIN MEASURE: Self-reported receipt of mammography screening within 2 years of the end of the study. KEY RESULTS: The median follow-up period for participants in this analysis was 17.8 months. In weighted multivariable logistic regression analyses, women in the intervention group had significantly higher odds of being up to date on mammography screening at the end of the follow-up period compared to women in the control group (odds ratio [OR] 2.26, 95 % confidence interval [CI]1.59–3.22). The effect of the intervention was stronger among women who were not up to date with mammography screening at enrollment (OR 3.63, 95 % CI 2.09–6.38). CONCLUSION: Patient navigation among urban African American Medicare beneficiaries increased self-reported mammography utilization. The results suggest that patient navigation for mammography screening should focus on women who are not up to date on their screening.